Fields of opportunity: a mixed-methods analysis of agritourism entrepreneurship in Kansas - Reyes, Mia Laura (My University, 2026)
Faced with threats such as climate change and market volatility, U.S. agricultural producers are increasingly turning to agritourism to diversify income and build resilient businesses. While this combination of agriculture and tourism offers economic opportunities, it requires producers to adopt new aspects of an entrepreneurial mindset, exposing them to unique challenges generic agritourism resources often fail to address. There is a need to know how agritourism operators, particularly in Kansas, navigate these challenges to develop the entrepreneurial knowledge necessary for success. Therefore, this study utilized a sequential, exploratory, mixed-methods approach informed by entrepreneurial learning to achieve two overarching research aims related to agritourism entrepreneurship. Phase One (Chapter 2) described a sample of prospective and established agritourism operators’ (N = 54) transformation of experience into specialized, usable entrepreneurial knowledge. Through seven semi-structured focus groups and three interviews with existing and prospective agritourism operators in Kansas, the findings highlight the need for tailored support systems, including industry-specific mentoring, financial incentives, and targeted workshops. Phase Two (Chapter 3) employed audience segmentation and cluster analysis to characterize prospective and established agritourism operators (N = 93), focusing on their perceived levels of entrepreneurial self-efficacy, persistence, and alertness. Additionally, respondents identified their preferred communication methods, their trust in information sources, and their willingness to be involved in policy development. Ultimately, this study provides insight for scholars and practitioners interested in developing the agritourism industry and offers a first-hand account of the entrepreneurial barriers and opportunities faced by Kansas operators.
Keywords: Agritourism; Entrepreneurship; Mixed-methods